Permafrost spatial and temporal variations near Schefferville, Nouveau-Québec - Nicholson, Frank (Géographie physique et Quaternaire, 1979)
Specially detailed studies of permafrost have developed at Schefferville because of the availability of long term data and the economic stimulus of the effect of permafrost on the iron mines. Knowledge of the three dimensional distribution of permafrost has been greatly expanded and energy budget studies have given confidence to many aspects of interpretation. Although the mean annual temperatures are -5 to -6.5°, large areas remain free of permafrost due to the winter insulation provided by deep snow which accumulates where snow drifting is subdued (e.g. in woodland). There are large year to year variations of frozen ground temperature in the upper 25 m (due to variations of snow conditions) and active layer depth (related to variations of summer weather conditions). Suprapermafrost groundwater movement is often concentrated along specific channels and transported heat causes very deep active layers (up to 12 m) or even maintains unfrozen zones (up to 30 m). On simple sites the active layer is primarily related to % vegetation cover, with mean depth ranging from 2.3 m under 100% vegetation to 3.6 m under bare ground. Considerable effort has been devoted to quantifying snow data for permafrost prediction and good results have been obtained from quanti-titavely relating ground temperatures to snow and a simulated groundwater measure. The permafrost is generally in balance with the present climate and new permafrost has developed in mine waste dumps.